Características nutricionais do azevém sob doses de nitrogênio e desempenho de cordeiros terminados em sistema integração lavoura pecuária - Pereira, Juliana Reolon (2019)
With the objective of implanting new technologies in the agricultural systems many producers adhere to the integrated systems being able to produce in the same area meat, milk, wool and grains. In order for the system to have a positive effect, adequate soil and pasture management with correct fertilization, animal load control and crop rotation are ideal. The use of nitrogen in the pasture adds qualitative value and tends to increase the weight gain per area. The objective of the present work was to evaluate the effect of nitrogen in a grazing cycle on ryegrass (Lolium multiflorum Lam.) And its influence on the nutritional quality and on the performance of lambs at the end of the crop integration system. The experiment was developed at Unicentro (CEDETEG) in Guarapuava. The experimental area was composed of ryegrass (Jumbo HQ), receiving nitrogen fertilization applied in coverage in a single time at doses 0, 75, 150 and 225 kg ha-1 of N in winter and used for grazing by finishing lambs. The continuous grazing method was used with a variable stocking rate. The nutritional variables of the pasture were obtained after the collection of the material and later it was taken to the laboratory of bromatology for determination of DM, MM, OM, EE, CP, NDF, ADF, TC, fractionation of carbohydrates and nitrogen compounds. The pasture dry matter production, nitrogen fertilization efficiency and nitrogen recovery were evaluated in the pickets. The performance measures were obtained through weighing and evaluated the performance by area controlling the number of animals and the animal load. For each kg of N applied in the pasture, linear increases of 8.94 kg ha-1 of forage mass produced were observed. The CP levels also showed an increase in relation to the N rates, which presented a 138% increase in relation to the non application of N. The forage supply did not present a difference between nitrogen doses. The average weight gain of the animals did not change according to the nitrogen doses, but the weight gain per area increased from 2.62 kg LW ha-1 obtained at dose 0 to 13.09 kg LW ha-1 at the dose 225 kg ha-1 of N, presenting an increase of 191% from the zero dose for the dose 225 kg ha-1 of N. The nitrogen fertilization has a positive effect on the ryegrass pasture raising the pasture quality and increasing the weight gain per area.